An Analytical Study of Differentiated Instruction Strategies in Narrative Text Teaching at Junior High School - Adawiyah, Aisyah; Christanti, Ana (Journal of English Language and Education, 2025)
This research aims to analyze the implementation of differentiated instruction in teaching narrative texts of 8th-grade students at SMP Islam Sidoarjo and to evaluate students' narrative writing within this approach. Numerous studies have investigated the students' comprehension of narrative material in general. Therefore, this study attempts to fill this gap by focusing on Indonesia's fairy tales and legends. The research employed a descriptive qualitative method. The analysis of students' writing focused on five components: content, organisation, language use, grammar, and mechanics. Showed higher achievement in content understanding, with lowest performance in mechanics and language use. The results indicate that differentiated instruction enhances students' engagement and comprehension in narrative writing, though further focus is needed on improving technical writing aspects. The findings revealed that the English teacher implemented differentiated instruction by adjusting content, process, and product based on students' readiness, interests, and learning profiles. Other findings show that teachers did not conduct diagnostic tests to determine group based on students' learning styles. Therefore, it is important for further researchers to pay attention to teacher abilities when implementing differentiated learning, so that no steps are missed. This research contributes to providing insights for teachers in optimizing differentiated instruction in English writing.